2020
DOI: 10.3390/electronics9122141
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interface Trap on Transient Negative Capacitance Effect: Phase Field Model

Abstract: Ferroelectric materials have received significant attention as next-generation materials for gates in transistors because of their negative differential capacitance. Emerging transistors, such as the negative capacitance field effect transistor (NCFET) and ferroelectric field-effect transistor (FeFET), are based on the use of ferroelectric materials. In this work, using a multidomain 3D phase field model (based on the time-dependent Ginzburg–Landau equation), we investigate the impact of the interface-trapped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…This is because the voltage drop distribution dominates the ferroelectric switching behavior but other factors such as charge-assisted polarization also play a role. 22 Therefore, the E IL of the capacitor with scavenging at V sw , which was the same as that of the capacitor without scavenging when only the voltage drop distribution is considered in Fig. S1b, † will be slightly higher than that of the capacitor without scavenging.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…This is because the voltage drop distribution dominates the ferroelectric switching behavior but other factors such as charge-assisted polarization also play a role. 22 Therefore, the E IL of the capacitor with scavenging at V sw , which was the same as that of the capacitor without scavenging when only the voltage drop distribution is considered in Fig. S1b, † will be slightly higher than that of the capacitor without scavenging.…”
Section: Resultsmentioning
confidence: 87%
“…This is because the voltage drop distribution dominates the ferroelectric switching behavior other factors such as charge-assisted polarization also play a role. 22 Therefore, the E IL of the capacitor with scavenging at V sw , which was the same as that of the capacitor without scavenging when only the voltage drop distribution is considered in Figure 1Sb, will be slightly higher than that of the capacitor without scavenging. But since the charge-assisted polarization is less in the capacitor with scavenging, the damage caused by trapping will be also less, further measurements are required to compare reliability properties.…”
Section: Effect Of Oxygen Scavenging On Ferroelectricity Of Hzo-based...mentioning
confidence: 87%
See 1 more Smart Citation
“…Recently, an NC GAA-FET having a metal-ferroelectric-insulator-semiconductor (MFIS) type has been investigated by introducing NC characteristics to a gate stack as a nextgeneration semiconductor in a GAA transistor [19,20]. In addition, it has been reported that interface traps at the Si-SiO 2 interface can result in the degradation of transistor performance (e.g., sub-threshold swing) [21], the process-variable ∆V th [22], and negative bias temperature instability (NBTI)-induced ∆V th [23]. This interface trap effect has been considered important from before in silicon GAA-FET without ferroelectric material, and compact modeling methodologies have been proposed [24].…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] In particular, the interfacial charge trap density of ≈10 12 cm −2 is involved in breakdown and fatigue induced by charge trapping, [3,4] which causes issues of low endurance and read delay in FeFETs. [3,4,7] On the other hand, beneficial effects such as charge-assisted polarization [8] and leakage reduction [9] by IL are also exerted. Therefore, IL engineering to reduce thickness and unnecessary charge trapping is a promising direction in improving FeFET performances such as switching voltage (V sw ), memory window (MW), endurance, and retention properties.As attempts for IL engineering, methods such as the insertion of the additional IL, the modification by plasma treatment, and the inhibition of the IL formation have been reported.…”
mentioning
confidence: 99%